Modified aluminum-lithium alloy material as well as preparation method and application thereof
By performing surface nitriding treatment on the aluminum-lithium alloy and mixing and reacting with organic amine dispersion, a dense silicon oxide coating layer is formed, which solves the problem of poor stability of aluminum-lithium alloy and improves its combustion performance.
Patent Information
- Application Number
- CN202411435448.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-07
AI Technical Summary
The aluminum-lithium alloy has poor stability in the air and is prone to react with oxygen or moisture, resulting in a degradation of combustion performance.
By heating the aluminum-lithium alloy with ethylene amine, a surface nitriding aluminum-lithium alloy is formed, and on this basis, the surface nitriding reaction is carried out to further reduce the activity of the surface lithium, and finally, the surface nitriding liquid is mixed. A dense silicon oxide coating is formed on the surface.
It effectively reduces the surface activity of aluminum lithium alloy, improves its stability in the air, and improves combustion performance.
Smart Images

Figure CN119387583A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a modified aluminum-lithium alloy material and a preparation method and application thereof. Background Art
[0002] Aluminum-lithium alloys are often used in solid propellant formulations due to their low melting and boiling points, low ignition temperature, and high heat release, and are widely used in aerospace and other fields. Compared with aluminum powder, aluminum-lithium alloys can effectively improve the specific impulse of solid propellants. At the same time, they are very likely to produce micro-explosion effects during combustion, which can greatly improve the problem of residue deposition after combustion. However, the lithium in aluminum-lithium alloys is highly active and easily reacts with oxygen or moisture in the air, destroying the surface structure of the particles, resulting in a decrease in the combustion performance of aluminum-lithium alloys.
[0003] In order to effectively improve the stability of aluminum-lithium alloy in air, Chinese patent document CN 116422877A discloses a method for stabilizing aluminum-lithium alloy powder by coating an organic silicon-oxygen system with a thiol reaction on the surface. Although this method reduces the hygroscopicity of the material to a certain extent, it also has a series of disadvantages: (1) The bonding force between the silicon oxide coated on the surface and the base material is poor and is easy to debond; (2) Since a layer of organic matter is coated between the silicon oxide and the aluminum-lithium alloy, the mass fraction of the inert substance coating of the final material is increased, thereby reducing the energy performance of the aluminum-lithium alloy; (3) Although the aluminum-lithium alloy material is coated, the lithium on the surface of the aluminum-lithium alloy material still exists, and the stability still needs to be improved.
[0004] Therefore, for aluminum-lithium alloys, how to further improve their stability is a current problem and difficulty. Summary of the invention
[0005] The technical problem solved by the present invention is to overcome the defect of poor storage stability of aluminum-lithium alloy in the prior art, and provide a modified aluminum-lithium alloy material and its preparation method and application. The modified aluminum-lithium alloy material prepared by the present invention has a dense and firm coating layer, which can effectively reduce the surface activity of the aluminum-lithium alloy and improve the storage stability of the aluminum-lithium alloy.
[0006] The present invention first heats the aluminum-lithium alloy and ethyleneamine to obtain the aluminum-lithium alloy after surface nitridation treatment. During this reaction, ethyleneamine is decomposed into free N atoms, C atoms and H2. The free N atoms will penetrate into the Al and Li atoms on the surface of the aluminum-lithium alloy, thereby reducing the activity of lithium on the surface of the aluminum-lithium alloy. Then, the aluminum-lithium alloy after surface nitridation treatment, organic solvent, surfactant and organic amine dispersion are mixed and reacted. During this reaction, the surfactant can disperse the aluminum-lithium alloy particles and prevent them from agglomerating. The organic amine can further react with the aluminum-lithium alloy after surface nitridation treatment to consume the lithium on the surface. The above two steps can further reduce the activity of lithium on the surface of the aluminum-lithium alloy. Finally, a hydrolysis promoter and a silane coupling agent are added to coat the surface of the aluminum-lithium alloy with a layer of dense silicon oxide. Based on the reduced activity of lithium on the surface of the aluminum-lithium alloy and the dense silicon oxide wrapped in the outer layer, the stability of the prepared modified aluminum-lithium alloy material is improved.
[0007] The present invention solves the above technical problems through the following technical solutions:
[0008] The present invention provides a method for preparing a modified aluminum-lithium alloy material, which comprises the following steps:
[0009] (1) heating a mixture of an aluminum-lithium alloy and ethyleneamine at 200-350° C. for 1-6 hours to obtain an aluminum-lithium alloy after surface nitridation treatment;
[0010] (2) The dispersion containing the aluminum-lithium alloy after the surface nitriding treatment, the organic solvent, the surfactant and the organic amine is mixed and reacted for 0.2-2 hours, then the temperature is raised to 40-80°C, and then a hydrolysis promoter and a silicon source are added and the reaction is continued for 2-24 hours to obtain the modified aluminum-lithium alloy material.
[0011] In step (1), the mass fraction of lithium in the aluminum-lithium alloy may be 3%-15%, for example 5%. The particle size of the aluminum-lithium alloy may be 1-100 μm, for example 29 μm or 40 μm.
[0012] In step (1), the ethyleneamine generally refers to an acyclic polymer product of ethylenediamine, preferably one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine and cyclic amine compounds (such as piperazine, aminoethylpiperazine, hydroxyethylpiperazine), more preferably one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
[0013] In step (1), the ethyleneamine is preferably further impurity-removed before use. The impurity-removing process preferably comprises the following steps: heating the ethyleneamine at 100-200° C. for 1-6 hours.
[0014] When the ethyleneamine is tetraethylenepentamine, the heating temperature is preferably 100-150° C. (eg, 120° C.), and the heating time is preferably 1-3 h (eg, 1.5 h).
[0015] In step (1), the ratio of the mass of the aluminum-lithium alloy to the volume of the ethyleneamine may be 0.02-2 g / mL, preferably 0.02-0.1 g / mL, for example 0.0625 g / mL.
[0016] In step (1), the preparation method of the mixture of aluminum-lithium alloy and ethyleneamine is preferably: adding aluminum-lithium alloy to ethyleneamine and mixing them evenly.
[0017] In step (1), the heating method can be conventional in the art, such as heating in an oil bath or on a heating table.
[0018] In step (1), the temperature of the heating reaction is preferably 240-320°C, such as 250°C, 270°C, 280°C, 290°C or 300°C.
[0019] In step (1), the heating reaction time is preferably 1.5-4 h, such as 2 h or 3 h.
[0020] In step (1), according to the conventional art, after the heating reaction is completed, filtration and drying are generally required. The filtration method can be conventional in the art, such as vacuum filtration. The drying is, for example, vacuum drying.
[0021] In step (2), the organic solvent is preferably one or more of methanol, ethanol, N,N-dimethylformamide and N-methyl-2-pyrrolidone, for example, N,N-dimethylformamide.
[0022] In step (2), the surfactant is preferably one or more of Span 80, Tween 80 and dioctyl adipate, for example, Span 80.
[0023] In step (2), the organic amine is preferably ethylenediamine and / or triethylamine, more preferably ethylenediamine.
[0024] In step (2), the ratio of the mass of the aluminum-lithium alloy to the volume of the organic solvent may be 0.05-2 g / mL, preferably 0.05-0.5 g / mL, such as 0.1 g / mL or 0.2 g / mL.
[0025] In step (2), the ratio of the mass of the aluminum-lithium alloy to the volume of the surfactant may be 5-50 g / mL, preferably 20-30 g / mL, such as 25 g / mL or 30 g / mL.
[0026] In step (2), the ratio of the mass of the aluminum-lithium alloy to the volume of the organic amine may be 5-50 g / mL, preferably 20-30 g / mL, such as 25 g / mL or 30 g / mL.
[0027] In step (2), the preparation method of the "dispersion containing the aluminum-lithium alloy after the surface nitriding treatment, an organic solvent, a surfactant and an organic amine" preferably includes: adding the aluminum-lithium alloy after the surface nitriding treatment into an organic solvent and mixing evenly, and then slowly adding the surfactant and the organic amine under stirring.
[0028] In step (2), the temperature of the mixed reaction of the "dispersion containing the aluminum-lithium alloy after the surface nitriding treatment, organic solvent, surfactant and organic amine" can be 15-40°C, for example 20°C; the time of the mixed reaction can be 0.5-1h, for example 0.5h.
[0029] In step (2), the hydrolysis promoting agent is preferably hydrochloric acid, ammonia water or deionized water.
[0030] In step (2), the silicon source is preferably one or more of tetraethyl silicate, 3-aminopropyl-trimethoxysilane, 1,2-bistrimethoxysilylethane and Na2SiO3·9H2O.
[0031] In step (2), the mass of the aluminum-lithium alloy and the volume of the silicon source may be 1:(0.02-0.2) g / mL, preferably 1:(0.04-0.1) g / mL, for example 1:0.08 g / mL.
[0032] In step (2), the volume ratio of the hydrolysis accelerator to the silicon source may be (0.1-1):1, for example, 0.5:1.
[0033] In step (2), the method of raising the temperature to 40-80° C. can be conventional in the art, such as an oil bath or a water bath.
[0034] In step (2), after adding the hydrolysis accelerator and the silane coupling agent, the reaction is preferably continued for 12-24 hours, for example 18 hours.
[0035] In step (2), according to the conventional art, after adding the hydrolysis accelerator and the silane coupling agent and continuing the reaction for 2-24 hours, filtration and drying are generally required. The filtration method can be, for example, vacuum filtration.
[0036] The present invention provides a modified aluminum-lithium alloy material prepared by the preparation method as described above.
[0037] In the present invention, in the modified aluminum-lithium alloy material, the mass fraction of silicon dioxide coated on the surface may be 2%-5%, for example, 3.52%, 3.56%, 3.72% or 3.75%.
[0038] The present invention provides an application of the modified aluminum-lithium alloy material as described above as a solid propellant component in the aerospace field.
[0039] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0040] The reagents and raw materials used in the present invention are commercially available.
[0041] The positive and progressive effects of the present invention are:
[0042] (1) The preparation method of the present invention is simple, low-cost, and suitable for large-scale production;
[0043] (2) The modified aluminum-lithium alloy material prepared by the present invention has a dense and firm coating layer, which can effectively reduce the surface activity of aluminum and lithium and improve the storage stability of the aluminum-lithium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a SEM image of the modified aluminum-lithium alloy material prepared in Example 4;
[0045] Figure 2 is the SEM image of the original aluminum-lithium alloy;
[0046] Figure 3 This is a picture showing the effect of the modified aluminum-lithium alloy material prepared in Example 4 after being left standing in water at room temperature for 3 hours;
[0047] Figure 4 This is a diagram showing the effect of the aluminum-lithium alloy raw material of comparative example 1 in water at room temperature. DETAILED DESCRIPTION
[0048] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0049] Example 1
[0050] Step 1: Heat 80 mL of tetraethylene pentamine in an oil bath to 120° C. and keep warm for 1.5 hours to remove impurities; add 5 g of aluminum-lithium alloy (lithium content of 5%, particle size of 29 μm) to the above solution, and continue stirring at 120° C. and 800 rpm for 30 minutes to uniformly disperse the particles in the solution to obtain dispersion A;
[0051] Step 2: The dispersion A is further heated to 250° C., stirred at a stirring rate of 800 rpm and kept warm for 2 hours, cooled to room temperature, filtered and dried to obtain an aluminum-lithium alloy after surface nitridation;
[0052] Step 3: Add 50 mL of N,N-dimethyl Formamide Stir at 800 rpm for 10 min to make the particle size uniform. Slowly add 0.2 mL of Span 80 and 0.2 mL of triethylamine to the solution, and continue stirring and reacting for 0.5 hours to obtain dispersion B;
[0053] Step 4: Heat the above dispersion B to 50°C using an oil bath, then add 0.2 mL of hydrochloric acid and 0.4 mL of tetraethyl silicate to the solution, respectively, and continue stirring at a stirring rate of 800 rpm for 18 hours. After the reaction is completed, filter and dry to obtain a modified aluminum-lithium alloy material.
[0054] Example 2
[0055] Step 1: Same as Example 1;
[0056] Step 2: Except that the reaction temperature is adjusted to 290° C., the other operations and conditions are the same as those in Example 1;
[0057] Step 3: Same as Example 1;
[0058] Step 4: Same as Example 1.
[0059] Example 3
[0060] Step 1: Same as Example 1;
[0061] Step 2: Except that the reaction temperature is adjusted to 290° C., the other operations and conditions are the same as those in Example 1;
[0062] Step 3: Except that 0.2 mL of triethylamine was replaced by 0.2 mL of ethylenediamine, the remaining operations and conditions were the same as those in Example 1;
[0063] Step 4: Same as Example 1.
[0064] Example 4
[0065] Step 1:
[0066] Step 2: Except that the reaction temperature is adjusted to 290° C., the other operations and conditions are the same as those in Example 1;
[0067] Step 3: Except that 0.2 mL of triethylamine was replaced by 0.2 mL of ethylenediamine, the remaining operations and conditions were the same as those in Example 1;
[0068] Step 4: Except for replacing 0.2 mL of hydrochloric acid with 0.2 mL of aqueous ammonia, the other operations and conditions are the same as those in Example 1.
[0069] Comparative Example 1
[0070] Aluminum-lithium alloy raw materials.
[0071] Effect Example
[0072] (1) Morphological characterization
[0073] Figure 1 This is a SEM image of the modified aluminum-lithium alloy material prepared in Example 4; Figure 2 This is the SEM image of the original aluminum-lithium alloy; by comparison, it can be found that the surface of the modified aluminum-lithium alloy material is smoother than that of the original aluminum-lithium alloy.
[0074] (2) Characterization of coating amount
[0075] The quality of the modified aluminum-lithium alloy materials prepared in Examples 1-4 after drying was tested respectively, and the quality of the aluminum-lithium alloy raw materials before coating was determined by The mass fraction of the surface-coated silicon dioxide was calculated by the formula, and the mass fractions of the coating layers in Examples 1-4 were 3.56%, 3.75%, 3.52% and 3.72%, respectively.
[0076] (3) Water stability test
[0077] The modified aluminum-lithium alloy materials prepared in the above Examples 1-4 were added to water respectively to observe the foaming conditions. The test results are shown in Table 1:
[0078] Table 1
[0079]
[0080] According to the test results, the modified aluminum-lithium alloy material prepared in Example 1 can be stably maintained in room temperature water (20°C) for 5 minutes without bubble generation, but the subsequent solution gradually becomes turbid, and bubbles appear and gradually increase, and it has a certain water stability; the modified aluminum-lithium alloy material prepared in Example 2 can be stably maintained in room temperature water (20°C) for at least 0.5h without bubble generation; the modified aluminum-lithium alloy material prepared in Example 3 can be stably maintained at 60°C for at least 2h without bubble generation; the modified aluminum-lithium alloy material prepared in Example 4 can be stably maintained at 60°C for at least 3h without bubble generation, and has good stability.
[0081] Figure 3 This is a picture showing the effect of the modified aluminum-lithium alloy material prepared in Example 4 after being left standing in water at room temperature for 3 hours; Figure 4This is a diagram showing the effect of aluminum-lithium alloy raw materials in room temperature water in comparative example 1. By comparison, it can be found that a large number of bubbles are immediately generated when the untreated aluminum-lithium alloy is placed in room temperature water, the reaction is violent, and the water stability is poor, while the modified aluminum-lithium alloy material prepared by the method of the present invention has good water stability.
[0082] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified aluminum-lithium alloy material, characterized in that: It includes the following steps: (1) heating a mixture of an aluminum-lithium alloy and ethyleneamine at 200-350° C. for 1-6 hours to obtain an aluminum-lithium alloy after surface nitridation treatment; (2) The dispersion containing the aluminum-lithium alloy after the surface nitriding treatment, the organic solvent, the surfactant and the organic amine is mixed and reacted for 0.2-2 hours, then the temperature is raised to 40-80°C, and then a hydrolysis promoter and a silicon source are added and the reaction is continued for 2-24 hours to obtain the modified aluminum-lithium alloy material.
2. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: The mass fraction of lithium in the aluminum-lithium alloy is 3%-15%; And / or, the particle size of the aluminum-lithium alloy is 1-100 μm; And / or, the ethyleneamine is one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine and cyclic amine compounds (such as piperazine, aminoethylpiperazine, hydroxyethylpiperazine), preferably one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
3. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: In step (1), the ethyleneamine needs to be cleaned before use; the cleansing process preferably includes the following steps: heating the ethyleneamine at 100-200° C. for 1-6 hours; And / or, in step (1), the ratio of the mass of the aluminum-lithium alloy to the volume of the ethyleneamine is 0.02-2 g / mL, preferably 0.02-0.1 g / mL; And / or, the preparation method of the mixture of aluminum-lithium alloy and ethyleneamine is: adding the aluminum-lithium alloy to ethyleneamine and mixing them evenly.
4. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: In step (1), the temperature of the heating reaction is 240-320°C, for example, 250°C, 270°C, 280°C, 290°C or 300°C; And / or, in step (1), the heating reaction time is 1.5-4h, such as 2h or 3h.
5. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: In step (2), the organic solvent is one or more of methanol, ethanol, N,N-dimethylformamide and N-methyl-2-pyrrolidone, such as N,N-dimethylformamide; And / or, in step (2), the surfactant is one or more of Span 80, Tween 80 and dioctyl adipate, for example, Span 80; And / or, in step (2), the organic amine is ethylenediamine and / or triethylamine, preferably ethylenediamine.
6. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: In step (2), the ratio of the mass of the aluminum-lithium alloy to the volume of the organic solvent is 0.05-2 g / mL, preferably 0.05-0.5 g / mL, such as 0.1 g / mL or 0.2 g / mL; And / or, in step (2), the ratio of the mass of the aluminum-lithium alloy to the volume of the surfactant is 5-50 g / mL, preferably 20-30 g / mL, for example 25 g / mL or 30 g / mL; And / or, in step (2), the ratio of the mass of the aluminum-lithium alloy to the volume of the organic amine is 5-50 g / mL, preferably 20-30 g / mL, such as 25 g / mL or 30 g / mL.
7. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: In step (2), the preparation method of the "dispersion liquid containing the aluminum-lithium alloy after the surface nitriding treatment, an organic solvent, a surfactant and an organic amine" comprises: adding the aluminum-lithium alloy after the surface nitriding treatment into an organic solvent and mixing them evenly, and then slowly adding the surfactant and the organic amine under stirring; And / or, in step (2), the temperature of the mixed reaction of the "dispersion containing the aluminum-lithium alloy after the surface nitriding treatment, the organic solvent, the surfactant and the organic amine" is 15-40°C; the time of the mixed reaction is 0.5-1h.
8. The method for preparing the modified aluminum-lithium alloy material according to claim 1, characterized in that: The hydrolysis promoting agent is hydrochloric acid, ammonia water or deionized water; And / or, the silicon source is one or more of tetraethyl silicate, 3-aminopropyl-trimethoxysilane, 1,2-bistrimethoxysilylethane and Na2SiO3·9H2O; And / or, in step (2), the mass of the aluminum-lithium alloy and the volume of the silicon source are 1:(0.02-0.2) g / mL, preferably 1:(0.04-0.1) g / mL; And / or, in step (2), the volume ratio of the hydrolysis promoter to the silicon source is (0.1-1):
1.
9. A modified aluminum-lithium alloy material obtained by the preparation method of the modified aluminum-lithium alloy material as described in any one of claims 1 to 8.
10. Use of the modified aluminum-lithium alloy material as claimed in claim 9 as a solid propellant component in the aerospace field.
Citation Information
Patent Citations
Method for realizing stabilization by coating organosilicon oxygen system on surface of aluminum-lithium alloy powder through sulfhydrylation reaction
CN116422877A